Banking risks and the role of value at risk in risk measurement - Oubira, Mohamed Said; Taibi, Abdellatif; Khedir, Okba (Journal of Ecohumanism, 2025)
This study seeks to shed light on the various approaches to risk measurement by drawing on both statistical techniques and financial analysis tools. Particular attention is devoted to the Value at Risk (VaR) approach, which is widely regarded as one of the most important quantitative measures of financial risk. The relevance of VaR stems from the advantages it offers, notably the relative simplicity and speed of its computation, as well as its ability to provide a single, concise numerical estimate that captures the magnitude of risk an underlying financial instrument may be exposed to. Owing to these features, VaR has become one of the most extensively adopted methods by financial institutions and market participants as a means of anticipating and mitigating potential losses, especially in a financial environment increasingly characterized by recurrent crises and successive shocks.